The Hesitancy of Seventh-day Adventist Members Toward Covid-19 Vaccine in Indonesia - Triwahyuni, Palupi; Zebedeus, Davied Yosua Abraham (8ISC Abstract Proceedings, 2022)
The growing coronavirus disease (COVID-19) cases have increased rapidly as an infectious disease caused by its newly developed variants. Particularly in Indonesia, positive confirmed cases of COVID-19, as of July 19, 2021, reached 2,877,476, with a death toll of 73,582 people. Indonesia ranked later as the first country with the highest active COVID-19 cases globally and then crowned as the number one country as the epicenter of the COVID-19 pandemic in Asia and the world. Due to this inevitable urgency, the government seeks various ways to prevent the transmission of the virus to the people. On the one hand, the health protocols go into strict implementation, namely, using masks, washing hands, keeping distance, avoiding crowds, and reducing mobility. On the other hand, the government also organizes a national vaccination program for all levels of society for free. Therefore, this research intently investigates the hesitancy of the Seventh-day Adventist (SDA) members in response to the COVID-19 vaccine in Indonesia. This study uses qualitative methods with the phenomenology approach, while there are fourteen informants on this study, consisting of SDA adult members with knowledge of this issue. Most of the respondents have shown similar answers regarding their doubts about the contents inside the COVID-19 vaccine. The researchers gather specific data utilizing a survey with purposive sampling through an in-depth interview. The research primarily operates Coallizi's method in the interview results. Keywords : Church members, Covid-19, vaccine, hesitancy, Indonesia